Isolation and Characterization of a Serratia rubidaea from a Shallow Water Hydrothermal Vent - Ricardo F. S. Pereira; Maria J. Ferreira; M. Conceição Oliveira; Maria C. Serra; Carla C. C. R. de Carvalho (Marine Drugs, 2023)
Microbial life present in the marine environment has to be able to adapt to rapidly changing and often extreme conditions. This makes these organisms a putative source of commercially interesting compounds since adaptation provides different biochemical routes from those found in their terrestrial counterparts. In this work, the goal was the identification of a marine bacterium isolated from a sample taken at a shallow water hydrothermal vent and of its red product. Genomic, lipidomic, and biochemical approaches were used simultaneously, and the bacterium was identified as Serratia rubidaea. A high-throughput screening strategy was used to assess the best physico-chemical conditions permitting both cell growth and production of the red product. The fatty acid composition of the microbial cells was studied to assess adaptation at the lipid level under stressful conditions, whilst several state-of-the-art techniques, such as DSC, FTIR, NMR, and Ultra-High Resolution Qq-Time-of-Flight mass spectrometry, were used to characterize the structure of the pigment. We hypothesize that the pigment, which could be produced by the cells up to 62 °C, is prodigiosin linked to an aliphatic compound that acts as an anchor to keep it close to the cells in the marine environment.